Pengaruh Scientific Approach Melalui Aplikasi Zoom Meeting terhadap Keaktifan Belajar Siswa - Suswandari, Meidawati (GERAM: Gerakan Aktif Menulis, 2021)
This study aims to determine the effect of the scientific approach through the zoom meeting application on the learning activeness of students at Palur 3 Elementary School. The research method uses quantitative research. The research design used a pre post test from the control class and the experimental class. The independent variable in this study is a scientific approach through the zoom meeting application. The dependent variable in this study is student learning activeness. The research was conducted in grade V of the 3 Palur Elementary School. The data collection tool used was a questionnaire. The data analysis technique uses the analysis prerequisite test which includes the normality test and the homogeneity test which is then followed by the hypothesis test (t-test) using SPSS. The results showed that the scientific approach through the Zoom meeting media influenced the learning activeness of the fifth grade students of SD Negeri 3 Palur. This can be seen from the results of the analysis test using the Paired Sample Test, the tcount was 9,143 with Sig 2 tailed of 0,000 with a t-table value of 2.101, indicating that tcount> ttable was 9.143> 2.101.